2017
DOI: 10.3390/ijerph14101231
|View full text |Cite
|
Sign up to set email alerts
|

Non-Traditional Risk Factors of Albuminuria in the Pediatric Population: A Scoping Review

Abstract: The presence of albumin in urine has been used for more than four decades as a marker of renal and cardiovascular damage. Most of the information on this marker is related to adults. The prevalence of albuminuria in the pediatric population has been reported as being 2.2–12.8% in some countries. Most research in this field is related to albuminuria and diseases, such as diabetes and hypertension. Using the methodology described by Arksey and O’Malley in 2005, a scoping review was carried out to show that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
5
1
Order By: Relevance
“…Our results show an alarming prevalence of albuminuria in the children of this rural community. The observed prevalence was almost three to five times higher than international literature reports (45.7% vs. 2.2% to 12.8%) [ 8 , 9 , 10 , 11 ]. It is important to mention that 30.3% of the children from the community were not taken into account for the calculation of the prevalence.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Our results show an alarming prevalence of albuminuria in the children of this rural community. The observed prevalence was almost three to five times higher than international literature reports (45.7% vs. 2.2% to 12.8%) [ 8 , 9 , 10 , 11 ]. It is important to mention that 30.3% of the children from the community were not taken into account for the calculation of the prevalence.…”
Section: Discussioncontrasting
confidence: 63%
“…The overall prevalence of albuminuria, as defined by an ACR greater than 30 mg/g, was 12.8% (95% CI 9.9–15.6). In males, the frequency of albuminuria was 10.2% (95% CI 6.1–14.2) and in females, it was 15.5% (95% CI 10.7–20.3) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, smoking was a risk factor for proteinuria. In adolescents, active smoking and secondhand smoke have been associated with decreased eGFR [68], and a relationship has been found between smoking and albuminuria in adult populations, as well as secondhand smoke exposure and proteinuria in children with chronic kidney disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors including industrial growth, environmental pollution, and the use of food containers and chemical products have been posited as probable causes for the prevalence of proteinuria. Several studies have demonstrated evidence regarding the relationship between exposure to environmental factors such as bisphenol A (BPA), heavy metals (including lead, cadmium, and chromium), and cigarette smoking and direct kidney damage causing albuminuria in the pediatric population [13]. Additionally, exposure to ambient fine particulate matter with an aerodynamic diameter ≤2.5 μm (PM 2.5 ) negatively affects renal function in adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…Causes and characteristics of albuminuria in pediatric population are different from those in adults. 4,5 Unlike adults, orthostatic albuminuria is dominant in pediatric population. Therefore, compared to studies about the relation between HL and microalbuminuria (MIA) in adults, 6 pediatric studies for albuminuria were mostly performed for more prominent macroalbuminuria (MAA) such as nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%